Das Thermische Verhalten von Na₃[Fe(CN)₅SO(CH₃)₂]: H₂O - Baran, Enrique José (1976)
The thermal behaviour of Na₃[Fe(CN)₅SO(CH₃)₂]: H₂O has been investigated by thermogravimetry and diferential thermal analysis. The results are briefly discussed.